Edukasi Persiapan Diri Ibu dalam Menghadapi Persalinan untuk Menurunkan Tingkat Kecemasan dan Persiapan Mental Ibu di Poskeskel Batu Hampa - Elwitri Silvia; Ratih Septiana Arpen; Hanifa Zaini. S (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Childbirth is a process that must be prepared for because it plays a major role in how first-time mothers will develop good self-esteem, positive feelings for the baby and an easier adjustment to the role of mother. Fear and unpreparedness in facing childbirth will have a negative impact both during the birth process which will have an impact on the health of the mother and fetus as well as in the lactation process and optimizing mother and baby bonding. The aim of this community service activity is to provide education on the mother's self-preparation for childbirth including the importance of preparing for childbirth, the mother's self-preparation for childbirth, self-empowerment that pregnant women can do in preparing themselves for the birth process, the importance of positioning during pregnancy to optimize the position of the fetus. and presentation and re-demonstration of pregnancy exercises. Activities were carried out at the Poskeskel Batu Hampa involving local village midwives and health cadres. This activity was very positively welcomed by the village midwives and participants as evidenced by the enthusiasm of the participants in participating in the activity. Hopefully this activity can become a routine agenda so that it becomes a provision for pregnant women when facing childbirth.